A RECORD OF DERBIDAE (INSECTA: HOMOPTERA: FULGOROIDEA) IN THE MIOCENE OF THE NORTHERN CAUCASUS - Emeljanov A.F. (My University, 2002)
The second fossil species of the tribe Otiocerini sensu stricto (Derbidae), Mysidioides migdisovae sp. nov. from the Miocene of Stavropol is described. It belongs to a genus now distributed in Palearchearctica and in the Oriental and Ethiopian Realms.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен